From Light Chain Deposition to Multiple Myeloma - Case Report and Literature Review - Domingos, A (2020)
Monoclonal gammopathies consist of a broad spectrum of diseases, ranging from asymptomatic monoclonal gammopathy of undetermined significance to multiple myeloma (MM). Multiple myeloma is a malignant plasma cell disorder and accounts for 10% of all hematological malignancies and 1% of all malignancies. Differential diagnosis may be challenging, considering the variety of clinical entities with similar behavior. About 15 -20% of MM only secretes monoclonal light chains, called light chain MM, which is associated with poorer outcome. Two intermediate concepts were recently introduced, monoclonal gammopathy of renal significance (MGRS) and a wider concept of mono clonal gammopathy of clinical significance (MGCS). The former behaves as a clonal proliferative disorder with associated nephrotoxicity, but does not have the hematological criteria for MM, while MGCS expands this concept to other organs. A subtype of MGCS is monoclonal immunoglobulin deposition disease, a multisystemic disorder characterized by light or heavy chain deposition of monoclonal immunoglobulin in various organs and encompasses three clinical entities: Light -Chain, Light - and Heavy -Chain, and Heavy -Chain Deposition Disease (LCDD, LHCDD and HCDD, respectively). We describe an unusual case of LCDD in which MM was subsequently considered although the proposed criteria are not met. We demon strate the variability of clinical -pathological presentation of LCDD, requiring a rapid decision -making, particularly in terms of kidney and survival outcomes